2016
DOI: 10.5812/numonthly.36022
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Perineural Invasion in Prostate Needle Biopsy Specimens and Pathologic Staging After Radical Prostatectomy

Abstract: BackgroundProstate cancer is the second most common malignancy among men worldwide and the sixth cause of cancer-related death. Some authors have reported a relationship between perineural invasion (PNI), Gleason score, and the invasion of peripheral organs during prostatectomy. However, it is not yet clear whether pathological evidence of PNI is necessary for risk stratification in selecting treatment type.ObjectivesThe clinical and pathological stages of prostate cancer are compared in patients under radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 25 publications
11
12
1
Order By: Relevance
“…finding was stated in the study of Niroomand et al(2).Other studies conducted by Saadat et al and Antunes et al presented similar results as well (9,15). In fact, it seems that, the PNI in prostatic cancer is mostly in association with the duration of malignancy in comparison to age of www.nephropathol.com Journal of Nephropathology, Vol 8, No 4, October 2019 Perineural invasion and PSA 3 patients, though duration of this malignancy may have been longer among older patients.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…finding was stated in the study of Niroomand et al(2).Other studies conducted by Saadat et al and Antunes et al presented similar results as well (9,15). In fact, it seems that, the PNI in prostatic cancer is mostly in association with the duration of malignancy in comparison to age of www.nephropathol.com Journal of Nephropathology, Vol 8, No 4, October 2019 Perineural invasion and PSA 3 patients, though duration of this malignancy may have been longer among older patients.…”
supporting
confidence: 82%
“…In addition, Jeon et al presented that PSA level and Gleason score were significantly higher among patients who had PNI (16). On the other hand, Niroomand et al presented contrary results in their study which was conducted on over 500 patients with prostate cancer (2). This difference may be attributed to different studied samples among the studies.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A meta‐analysis concluded that PNB PNI positivity was a significant marker to predict T3 disease and may be included in new nomograms [18]. A recent study found that PNB PNI positivity was correlated with high stage disease; however it was stated that this finding was not significant alone [19]. In spite of this study result, the majority of studies determined a correlation with T3 disease and in our study PNB PNI positivity was correlated with T3 disease, high GS, tumor volume and surgical margin positivity; however it was not significant alone.…”
Section: Discussionmentioning
confidence: 99%